Review of sport injures for teams and athletes - Zenkova T.A.; Shengelaya S.A.; Groshevikhin I.V.; Chabovskiy S.Yu. (Theory and Practice of Physical Culture, 2024)
Objective of the research was to analyses the causes and conduct a comparative analysis of the causes and consequences and the incidence of injuries for sport teams and athletes. Methods and structure of the study. The athletes’ sports activities were analyzed based on parameters such as volume, intensity, and number of competitions, as well as the nature and intensity of sports injuries. The experiment involved 150 student athletes from the technical school of the Rostov State University of Railway Engineering. The athletes’ sports activities were analyzed based on parameters such as volume, intensity, and number of competitions, as well as the nature and intensity of sports injuries. The sports disciplines presented included track and field, swimming, judo, table tennis, basketball, football, and volleyball. Results and conclusions. It was found that the injury rate was significantly higher in team sports compared to individual sports (62% in team sports, 38% in individual sports). Based on the number of injuries sustained during competitions and training activities, it was concluded that team sports athletes have a higher injury rate – 2,6 persons/injuries versus 1,7 persons/injuries in individual sports. Participation in team sports is associated with a higher risk of injury regardless of the intensity of the load.